The Socialization of Children from Vietnamese - Korean Multicultural Families: A Case Study of Korean International Schools in Hanoi and Ho Chi Minh City - Duong Quynh Thu, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
From the moment of birth, an individual exists as a biological entity. However, true integration into human society necessitates the acquisition of cultural norms, values, knowledge, and beliefs specific to their given community. This process involves adapting to social roles and cultural practices, ultimately enabling effective communication and fulfillment of societal responsibilities. Notably, language assumes a pivotal role in this intricate web of socialization and stands as arguably the most influential factor in the overall process. To delve into the current state of socialization among children from Vietnamese-Korean multicultural families residing in Vietnam and attending a Korean International School, this research employs socialization theory, descriptive statistical methods via questionnaires, and interdisciplinary research techniques.Received 15th April 2024; Revised 5th June 2024; Accepted 7th August 2024